أثر أنماط أساليب المحاسبة الإبداعية على جودة المعلومات المحاسبية وانعكاساتها على درجة الثقة في القوائم المالية - عبدالباقي، أميرة عبدالرحمن مكي; موسى، الطيب حامد إدريس (جامعة الأزهر - كلية التجارة, 2021)
تتمثل مشكلة البحث في نتيجة الممارسات والإجراءات والسياسات المتبعة التي يقوم بها المحاسبين مستغلين ذكائهم ومعرفتهم وخبرتهم بالمعايير المحاسبية للتلاعب بالأرقام بهدف تحسين صورة الوحدة الاقتصادية وإعطاء بيانات مضللة نتيجة ممارسة المحاسبة الإبداعية، ويهدف البحث إلى التعرف على أهم أساليب المحاسبة الإبداعية التي تمارسها إدارة الشركات للتأثير على جودة المعلومات المحاسبية التي تعرضها القوائم المالية ومدى تأثيرها على درجة الثقة في هذه القوائم. وأسباب ودوافع أساليب التلاعب والتي تؤدي إلى زعزعة ثقة مستخدمي هذه المعلومات المحاسبية في القوائم المالية وبيان أهم الوسائل التي يمكن استخدامها للتقليل من أثارها على قراراتهم الاستثمارية. واستخدم الباحثان المنهج الاستنباطي عند اختيار مشكلة الدراسة ووضع الفروض العلمية بالإضافة إلى التحليل الإحصائي الذي تم الاعتماد عليه في الدراسة الميدانية، يتمثل مجتمع عينة الدراسة في مجموعة من المحاسبين والمراجعين والأكاديميين، ومن أبرز النتائج أن التلاعب في نسبة إهلاك الأصول طويلة الأجل تؤثر على بنود قائمة المركز المالي ويوصى البحث بإعادة تأهيل المحاسبين وذلك من خلال التعرف على أساليب المحاسبة الإبداعية لتحقيق جودة المعلومات المحاسبية التي تعرضها القوائم المالية. The research problem is that the outcome of the accountants practices, procedures, and policies; getting use their intelligence, knowledge, and experience with accounting standards so that to manipulate numbers in order to improve the image of the economic unit and give misleading data as a result of creative accounting practice. The research aims to identify the most important creative accounting methods practiced by corporate management to influence the quality of the accounting information presented by the financial statements and their effect on the degree of trusting in these statements. Moreover, the research aims to study the reasons and motives for manipulating methods that lead to undermining the confidence of the users of this accounting information in the financial statements. In addition to present the mechanisms and methods that can be used to reduce its effects on their investment decisions. The researchers used the deductive approach when choosing the study problem, and setting scientific hypotheses, in addition to the statistical analysis that was relied upon in the field study. The sampling used is a group of accountants, auditors and academics. One of the most prominent results is that the manipulation of the ratio of long-term asset depletion affects the items of the center’s list. The researchers recommend that financial research is should be adopted to rehabilitate accountants, by identifying creative accounting methods to achieve the quality of accounting information presented in the financial statements.
Keywords: إدارة الأعمال -- المعايير المحاسبية -- الوحدة الاقتصادية -- الاحتيال المحاسبي -- التدفقات النقدية